Label‐free imaging of non‐deparaffinized sections of the human kidney to determine tissue quality and signatures of disease. Issue 3 (8th February 2022) - Sabo, Angela R.; Winfree, Seth; Bledsoe, Sharon B.; Phillips, Carrie L.; Lingeman, James E.; Eadon, Michael T.; Williams, James C.; El‐Achkar, Tarek M.
Abstract: Label‐free fluorescence imaging of kidney sections can provide important morphological information, but its utility has not been tested in a histology processing workflow. We tested the feasibility of label‐free imaging of paraffin‐embedded sections without deparaffinization and its potential usefulness in generating actionable data. Kidney tissue specimens were obtained during percutaneous nephrolithotomy or via diagnostic needle biopsy. Unstained non‐deparaffinized sections were imaged using widefield fluorescence microscopy to capture endogenous fluorescence. Some samples were also imaged with confocal microscopy and multiphoton excitation to collect second harmonic generation (SHG) signal to obtain high‐quality autofluorescence images with optical sectioning. To adjudicate the label‐free signal, the samples or corresponding contiguous sections were subsequently deparaffinized and stained with Lillie's allochrome. Label‐free imaging allowed the recognition of various kidney structures and enabled morphological qualification for adequacy. SHG and confocal imaging yielded quantifiable high‐quality images for tissue collagens and revealed specific patterns in glomeruli and various tubules. Disease specimens from patients with diabetic kidney disease and focal segmental glomerulosclerosis showed distinctive signatures compared to specimens from healthy controls with normal kidney function. Quantitative cytometry could also be performed when DAPI is added in situ before imaging. These results show that label‐free imaging of non‐deparaffinized sections provides useful information about tissue quality that could be beneficial to nephropathologists by maximizing the use of scarce kidney tissue. This approach also provides quantifiable features that could inform on the biology of health and disease. Abstract : Label‐free non‐deparaffinized sections provides useful information about tissue quality that could be beneficial to nephropathologists. This approach also provides quantifiable features that could inform on the biology of health and disease.